Landasan Filosofis, Sosiologis dan Yuridis terhadap Positivisasi Perceraian di Pengadilan Agama - Akhmad Farroh Hasan (Journal of Law, Society, and Islamic Civilization, 2022)
According to Islamic law, divorce can occur on one side, namely the husband saying Thalaq. but in the KHI article 115 and the Marriage Law Article 39 paragraph (1) of the Marriage Law that "Divorce can only be carried out before a court session after the court in question tries and fails to reconcile the two parties (husband and wife). Obedience to Allah's law is an absolute obligation for Muslims and as the people of Indonesia, we are also obedient to the prevailing laws and regulations of the Republic of Indonesia. The research is a normative legal research with a statutory approachand a conceptual approach, with the aim of providing a philosophical, sociological and juridical basis on the positivization of divorce in religious courts. The research produced findings including: First, philosophically, KHI and Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage to provide the benefit of mankind in accordance with the purpose of the law was made. Second, sociologically, with the principle of making it difficult for divorce to occur, it will inhibit the increase in divorce in society. Third, Juridical provides legal certainty and legal protection as a result of divorce.